2013
DOI: 10.1159/000351843
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Use of Cetirizine in the Treatment of Allergic Rhinitis

Abstract: Background: Cetirizine is among the first second-generation H1 antihistamines (SGAHs) developed to provide selective H1 receptor inhibition without central nervous system depression. Objective: The aim of this review is to summarize the amount of data collected over 25 years of clinical use of cetirizine and compare this with data available for other SGAHs in the management of patients with allergic rhinitis (AR). Methods: A comprehensive literature search for publications relating to cet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 74 publications
0
25
0
4
Order By: Relevance
“…The International Study of Asthma and Allergies in Childhood Phase 3 reported that the prevalence rates of allergic rhinitis in Indonesia in children aged 6-7 years and 13-14 years were 3.6% and 6.4%, respectively [9]. Several studies have evaluated the inflammatory properties of cetirizine in children and adults with allergic rhinitis [10].…”
Section: Discussionmentioning
confidence: 99%
“…The International Study of Asthma and Allergies in Childhood Phase 3 reported that the prevalence rates of allergic rhinitis in Indonesia in children aged 6-7 years and 13-14 years were 3.6% and 6.4%, respectively [9]. Several studies have evaluated the inflammatory properties of cetirizine in children and adults with allergic rhinitis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Oral bioavailability of cetirizine is more than 70% and shows high intestinal absorption in human. 7,24 P-gp activity undoubtedly plays an important role in limiting intestinal permeability of BCS class II-IV P-gp substrates (not for BCS class I compounds). The high Pgp expression levels in the intestine make the moderately absorbed P-gp substrates more susceptible to P-gpmediated efflux.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we used a suitable histamine-1 receptor antagonist that has been shown to be well tolerated with favourable pharmacological properties in other patient populations. 18 In addition, the effects of cetirizine have been studied previously in patients with psoriasis. 12,19 A limitation of our study is the relatively small sample size, owing to our prestudy power calculation.…”
Section: Discussionmentioning
confidence: 99%